Antibiotic resistance pattern and biofilm production in Staphylococcus aureus isolates and Staphylococcus epidermidis isolated from hospital infections Tehran in 2016 - Sina Mashaiekhi; Kumarss Amini (مجله دانشگاه علوم پزشکی بیرجند, 2018)
Background and Aim: Staphylococci are common pathogens of humans and livestock that able to produce a wide range of diseases. Staphylococcus epidermidis and Staphylococcus aureus are the important factors for biofilm production in patients. This study was designed to determine the ability of  biofilm production and the resistance pattern of Staphylococcus epidermidis and Staphylococcus aureus strains that isolated from hospital and food infectious. Materials and Methods: This descriptive cross-sectional study was performed on 117 hospital samples. First, biochemical tests were used in order to isolate and confirm Staphylococcus epidermidis and aureus strains. To determine biofilm production, the Microtiter plate method was applied and the presence of icaA and icaD genes are were identified using PCR. Antibiotic resistance pattern of strains was evaluated by Disk diffusion method related to 7 antibiotics. Results: 12 strains of Staphylococcus epidermidis and 20 strains of Staphylococcus aureus were isolated from 117 hospital samples by biochemical tests, of these, 6 strains of the Staphylococcus epidermidis and 16 strains of the Staphylococcus aureus were the producers of biofilm. PCR results shown that icaA and icaD genes were present in 15 strains of Staphylococcus aureus and 6 strains of the Staphylococcus epidermidis. The highest antibiotic resistance in the antibiotic resistance test was related to penicillin, gentamicin, and amikacin respectively. Conclusion: Extending clinical samples of biofilm producers with multiple antibiotic resistance can be considered as a serious risk for patients and lead to increase mortality rate in hospitals.